A case study on mapping air dryer capabilities from agile manufacturing perspectives. (1st January 2013) - Sreenivasa, C.G.; Devadasan, S.R.; Sivaram, N.M.; Karthi, S.
Pneumatic products employ compressed air to execute mechanical actions. The atmospheric compressed air contains moisture which is removed using air dryers. Specifications of the air dryers vary dynamically as the atmospheric compressed air is required to be dried for reaching varied dew points. This kind of dynamic variations can be faced if agile manufacturing (AM) criteria are adopted. The AM paradigm enables a company to respond quickly in accordance with the customers' dynamic demands. Considering the dynamic demands of the air dryers, the AM criteria need to be mapped with the characteristics of the air dryers. This paper reports a research in which this mapping exercise has been theoretically and practically carried out. The results of this exercise indicated that refrigeration and regenerative types of air dryers are found to possess maximum AM characteristics. The paper is concluded by appraising the need for more researches and applications in this direction.